Listening Materials for Vocational High School Students in Indonesia: Teachers’ Perception - Sularti Sularti; Nur Arifah Drajati; Slamet Supriyadi (Indonesian Journal of EFL and Linguistics, 2019)
Initially, communication is set up by listening. Students need the ability of listening skill for educational purposes and prepare themselves in social life. This study had the objective to investigate the perceptions of the teachers about the existing listening materials at the vocational high schools in Indonesia. In this study, the researcher engaged seventeen teachers of vocational high schools in Indonesia to be the participants. Data were collected by distributing a questionnaire then followed by an interview toward two participants. The results showed that listening materials met students’ needs, supported by the process of the scientific approach, were appropriate with the objective of the study and students' level of English, related to the syllabus of the 2013 curriculum model included the topic learned. On other hand, listening materials did not improve students’ ability in English, monotonous, made students having less focus, difficult to understand, difficult to build students’ prior knowledge, boring, and uninteresting. Finally, as the teachers’ view, the use of video could be the solution to the problems.